A novel double-ribonuclease toxin-antitoxin system linked to the stress response and survival of Acidovorax citrulli - Xudong Wang; Yumin Kan; Kaihong Bai; Xiaoli Xu; Xing Chen; Chengxuan Yu; Jia Shi; Na Jiang; Jianqiang Li; Laixin Luo (Microbiology Spectrum, 2023)
ABSTRACT Toxin-antitoxin (TA) systems are widespread among prokaryotes and can play an important role in the maintenance of genetic elements and pathogen virulence. Their roles in bacterial stress response and antimicrobial persistence currently remain highly controversial. The current study investigated a novel TA system (Aave_1720-Aave_1719) from the phytopathogenic bacterium Acidovorax citrulli, which had characteristics of both type II and type V TA systems. Heterologous expression in Escherichia coli confirmed that Aave_1720 functions as a toxin gene, while Aave_1719 acts as antitoxin gene. The Aave_1720 toxin functions as a ribonuclease, and antitoxin Aave_1719 binds directly to Aave_1720 to inhibit its ribonuclease activity, which is typical of type II TA systems. Interestingly, Aave_1719 itself was found to exhibit ribonuclease activity with a preference for targeting Aave_1720 mRNA, which indicates that it can also neutralize the Aave_1720 toxin in a manner characteristic of type V TA systems. Expression analysis revealed that the Aave_1719 gene is upregulated in response to sodium hypochlorite stress and that deletion of the Aave_1720 gene individually or in combination with Aave_1719 affected biofilm formation, as well as the survival of A. citrulli in response to sodium hypochlorite stress. Taken together, these findings expand our understanding of TA systems revealing a novel mechanism of toxin neutralization that combines aspects of both type II and type V TA systems. IMPORTANCE Bacterial fruit blotch (BFB), which is caused by the seed-borne bacterium Acidovorax citrulli, is a devastating disease affecting cucurbit crops throughout the world. Although seed fermentation and treatment with disinfectants can provide effective management of BFB, they cannot completely guarantee pathogen-free seedstock, which suggests that A. citrulli is a highly stress-resistant pathogen. Toxin-antitoxin (TA) systems are common among a diverse range of bacteria and have been reported to play a role in bacterial stress response. However, there is currently much debate about the relationship between TA systems and stress response in bacteria. The current study characterized a novel TA system (Aave_1720-Aave_1719) from A. citrulli that affects both biofilm formation and survival in response to sodium hypochlorite stress. The mechanism of neutralization differed from typical TA systems as two separate mechanisms were associated with the antitoxin, which exhibited characteristics of both type II and type V TA systems. The Aave_1720-Aave_1719 system described here also constitutes the first known report of a double-ribonuclease TA system in bacteria, which expands our understanding of the range of regulatory mechanisms utilized by bacterial TA systems, providing new insight into the survival of A. citrulli in response to stress.